Predictors of time-to-death on children in Tigray regional state, Ethiopia: a retrospective cross sectional study - Gebru Gebremeskel Gebrerufael; Bsrat Tesfay Hagos (BMC, 2021)
Abstract Background Although, the clinical and socioeconomic condition of Tigray Regional State mothers has been improved along with the decline in the child death rate. However, children's death rate is still one of the main community serious challenging issues of public health concern. Thus, the main objective of this current investigation was to identify the major predictor factors for short time-to-death in Children in the Tigray Regional State. Methods The study used a secondary data with cross-sectional study design. The information gathered was from 1018 childbirths 5 years prior to the survey. Independent variables such as mother's demographic variables, child demographic variables, healthiness and environmental factors were considered major hazard predictors of children's short time-to-death rate. This current investigation used bivariable and multivariable Cox regression model analysis to identify the major statistically significant associations with children's time-to-death rate. Results One thousand eighteen children under 5 years of age were included in the study. Of them, 50% of the children were males, and the median survival time-to-death of children was 26 months. Overall, the prevalence of experiencing child's death rate in the Tigray Regional State was 4.2%. The multivariable Cox regression model analysis showed that living rural place of residence (AHR = 19.8; 95% CI: (7.25-54.049)), being unvaccinated child (no) (AHR = 2.76; 95% CI: (1.071-7.11)), and poor wealth index (AHR = 15.4; 95% CI: (2.83-84)) were statistically significant predictors of time-to-death rate of children's. Conclusion The study recognized that being a rural place of residence, unvaccinated child status (no) and poor wealth index were statistically significant predictors of children's short time-to-death rate.